Fuzzy and Matlab/Simulink modelling of the air compression refrigeration cycle - Alsakarneh, Amjad (Strojniški vestnik, 2023)
The coefficient of performance (COP) for a gas refrigeration cycle was estimated using Matlab/Simulink and fuzzy logic. A Matlab/Simulink model of the gas refrigeration cycle was developed, and the output was compared to theoretical data. Additionally, fuzzy logic was used to estimate the COP for arbitrary low- and high-pressure levels. Simulation results were used to develop a multi-input-multi-output (MIMO) fuzzy Takagi-Sugeno-Kang (TSK)-based model. Both the Matlab/Simulink and the MIMO fuzzy model were found to be very well correlated with theoretical results, with an error of less than 2 %. These results demonstrate the effectiveness of using fuzzy logic to analyse gas refrigeration cycles and suggest that this approach can be extended to analyse other thermodynamic cycles.
Keywords: coefficient of performance; hladilni cikli; hladilno število; Matlab/Simulink; refrigeration cycles; Takagi-Sugeno-Kang